The study of titanium oxynitride coatings solubility deposited by reactive magnetron sputtering; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Leonova L. A. Liliya Aleksandrovna (2016, 2016)
Title screen